2020
DOI: 10.3390/rs12040613
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gridded Precipitation Datasets in Malaysia

Abstract: This study compares five readily available gridded precipitation satellite products namely: Climate Hazards Group Infrared Precipitation with Station Data (CHIRPS) at 0.05° and 0.25° resolution, Tropical Rainfall Measuring Mission Multi-Satellite Precipitation Analysis (TMPA 3B42v7) and Princeton Global Forcings (PGFv3), both at 0.25°, and Global Satellite Mapping of Precipitation Reanalysis (GSMaP_RNL) at 0.1°, and evaluates their quality and reliability against 41 rain gauge stations in Malaysia. The evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 43 publications
(49 reference statements)
2
8
0
Order By: Relevance
“…Furthermore, the validation of TRMM-3B42V7 over Malaysia and the neighboring regions also showed high consistency with ground observation [22][23][24][25][26][27]. A recent study by [28] showed that TRMM-3B42V7 is a reliable gridded…”
Section: Identify Bsl From Rainfall Datasupporting
confidence: 58%
“…Furthermore, the validation of TRMM-3B42V7 over Malaysia and the neighboring regions also showed high consistency with ground observation [22][23][24][25][26][27]. A recent study by [28] showed that TRMM-3B42V7 is a reliable gridded…”
Section: Identify Bsl From Rainfall Datasupporting
confidence: 58%
“…Therefore, it is necessary to further improve the observation ability of IMERG under heavy rainfall conditions. Ayoub et al (2020) and Prakash et al (2016), respectively, analyzed the precipitation accuracy of GSMaP satellite products and TMPA products in Malaysia and India, and the results showed that GSMaP could better detect the spatial distribution pattern of precipitation than TMPA, and the accuracy was the highest in summer. In addition, Aslami et al (2019), Zhou et al (2020) and Lu & Yong (2018) also compared the difference in precipitation accuracy between GSMaP and IMERG in Iran, mainland China and the Qinghai-Tibet Plateau, and found that the precipitation value estimated by IMERG was relatively close to the meteorological station record, and could replace the observation station in the study area where there was a lack of meteorological stations, thus having high hydrological simulation effect.…”
Section: Introductionmentioning
confidence: 99%
“…CHIRPS is a fusion of satellite images and data from rain-gauge stations. More detailed information on CHIRPS can be found in recent publications [32][33][34][35]. CHIRPS data perform well at the watershed scale.…”
Section: Study Area and Databasementioning
confidence: 88%
“…SPI is based on the normalized probability distribution (Figure 2), which can compare both the dryness and wetness in different regions. The numerical SPI value is extracted from a given probability distribution function [32,35,37]. Assume that x is the cumulated monthly precipitation in the selected time scale (1, 3, 6, 12 months), which fits a gamma probability density function g(x) as follows:…”
Section: Drought Severity Assessmentmentioning
confidence: 99%